Refractory diarrhea in a patient with Sjogren’s syndrome: A case report - Xu, Liling; Gui, Ming; Sun, Chuanzheng; Yau, Vicky; Sun, Chenyu; Qi, Jing (Frontiers in Nutrition, 2023)
We present the case of a 66-year-old man with no abdominal symptoms other than chronic refractory diarrhea. Other causes for diarrhea were excluded. The positive results of anti-SSA antibodies, Schirmer’s test, and the biopsy of minor salivary glands confirmed the diagnosis of Sjogren's syndrome. Moreover, during the course of treatment, the patient developed refeeding syndrome. His diarrhea and nutrition resolved with initiation of glucocorticoids. This case highlights that chronic refractory diarrhea can be the chief complaint and most severe symptom in patients with Sjogren's syndrome.